تأثير منهج تعليمي مقترح باستخدام أسلوبي التنافس الذاتي والتدريبي في تعلم مهارتي المناولة والاستلام بكرة اليد - مصطفى, ابراهيم محمد (Sulaimani Journal for Humanities, 2022)
The research aims to discover: Preparing a proposed educational curriculum using the self-competitive and training methods in learning the skills of handling and receiving handball. - Detecting the effect of the self-competitive and training methods in learning the skills of handling and receiving handball. - Identifying the differences between the two styles of self-competition and training in the post-test of the skills of handling and receiving handball. The researcher used the experimental method for its suitability to the nature of the research, and the research sample was the students of the second stage in the physical education school - Koya University, which numbered (24) students and by (12) students for each group. As for the training tools, the research tools were represented by the specific skill test in handball (handling and receiving). - There are statistically significant differences between the mean of the pre and post-measurements for the first experimental group (which uses the self-competition method) in the degrees of the skills of handling and receiving in favor of the post measurement. - There are statistically significant differences between the mean of the pre and post-measurements for the second experimental group (which uses the training method) in the degrees of handling and receiving skills in favor of the post measurement. - The self-competition group outperformed the training group in the rates of change in the post-measurement over the pre-measurement of the skills under study. In light of the conclusions, the researcher recommended. - Using self-competitive and training methods in teaching the skills of handling and receiving handball, because of its high effectiveness and impact on learning. - The necessity of using and diversifying multimedia in the physical education lesson because of its great importance in enriching the education process and increasing motivation and desire for education while saving effort and time for the student and the teacher.
Keywords: educational curriculum; selfcompetitive method; training method; handling and receiving skills; handball